The association between body posture and malocclusion - a literature review - Głogowska, Karen; Wojtas, Mikołaj; Kapica, Marcin; Momot, Karol; Żmijewska, Aleksandra; Sztybór, Mateusz; Krzyżanowska, Maria; Maleszewska, Monika; Piątkiewicz, Julia; Nowak, Gabriela (Journal of Education, Health and Sport, 2024)
Effective body posture entails the correct alignment of body parts in relation to each other and is crucial for preserving balance, stability, and the efficient operation of muscles and joints. The major types of posture abnormalities such as lordosis, kyphosis and scoliosis can lead to alterations in various areas of the body, such as stomatognatic system. The potential correlation between malocclusion and body posture remains a subject of controversy. The aim of this review is to investigate and evaluate the association between posture defects and malocclusion on the basis of literature. This literature review has analyzed 18 studies. Inclusion criteria: clinical researches published after 2010, regarding children and adults. PubMed and Google Scholar has been searched to identify the papers. In 18 analyzed studies, 2133 patients were enrolled (including 979 children aged 4-18). A positive correlation between scoliosis and different types of malocclusion has been proven by six papers. There are also other noteworthy dependencies, such as overjet and pelvic torsion, kyphosis and sagittal position of mandible, skeletal Class III and torticollis, cross bite and scapula plane. Adolescent Idiopathic Scoliosis significantly affects the stomatognathic system, leading to issues like crossbite, crowding, increased overjet, overbite, partial open bite, and midline deviation. Orthopedists should collaborate with orthodontists for comprehensive treatment, particularly during developmental stages.